Mechanically Robust Plasma-Activated Interfaces Optimized for Vascular Stent Applications - Santos, Miguel; Filipe, Elysse C.; Michael, Praveesuda L.; Hung, Juichen; Wise, Steven G.; Bilek, Marcela Mm M. (ACS Applied Materials and Interfaces, 2016)
The long-term performance of many medical implants is limited by the use of inherently incompatible and bioinert materials. Metallic alloys, ceramics and polymers commonly used in cardiovascular devices encourage clot formation and fail to promote the appropriate molecular signaling required for complete implant integration. Surface coating strategies have been proposed for these materials but coronary stents are particularly problematic as the large surface deformations they experience in deployment require a mechanically robust coating interface. Here, we demonstrate a single step ion assisted plasma deposition process to tailor plasma-activated interfaces to meet current clinical demands for vascular implants. Using a process control-feedback strategy which predicts crucial coating growth mechanisms by adopting a suitable macroscopic plasma description in combination with non-invasive plasma diagnostics, we describe the optimal conditions to generate highly reproducible, industry scalable stent coatings. These interfaces are mechanically robust, resisting delamination even upon plastic deformation of the underlying material and were developed in consideration of the need for hemocompatibility and the capacity for biomolecule immobilization. Our optimized coating conditions combine the best mechanical properties with strong covalent attachment capacity and excellent blood compatibility in initial testing with plasma and whole blood, demonstrating the potential for improved vascular stent coatings.